2005
DOI: 10.1111/j.1365-2230.2005.01841.x
|View full text |Cite
|
Sign up to set email alerts
|

Sun protection initiatives in Cornwall

Abstract: Recent evidence indicates that there are significant numbers of cases of malignant melanoma in the UK. In order to assess the current position with regard to sun awareness in Cornwall, a questionnaire survey of all state primary school heads (n = 123) and a survey of a random sample of GP practices (n = 9) was carried out. The data obtained were supported by visits to libraries and Tourist Information Centres at urban and rural centres--this enabled the identification of sun awareness literature. Key health pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…In 1995, a list of Seven Sun Awareness Guidelines was disseminated to all English schools to implement changes to the school policy, environment and curriculum (21). A number of follow-up studies indicated a first level of change based on these guidelines had been established in schools but more work needed to be done and more resources were required to be invested and the sun safety initiative applied consistently (7,21,28). Further follow up indicated that environmental support was considered key to altering behaviour in schools, for example, provision of a shaded outdoor area.…”
Section: What Is Already Known About Sun Exposure and Skin Cancer?mentioning
confidence: 99%
See 2 more Smart Citations
“…In 1995, a list of Seven Sun Awareness Guidelines was disseminated to all English schools to implement changes to the school policy, environment and curriculum (21). A number of follow-up studies indicated a first level of change based on these guidelines had been established in schools but more work needed to be done and more resources were required to be invested and the sun safety initiative applied consistently (7,21,28). Further follow up indicated that environmental support was considered key to altering behaviour in schools, for example, provision of a shaded outdoor area.…”
Section: What Is Already Known About Sun Exposure and Skin Cancer?mentioning
confidence: 99%
“…Solar ultraviolet radiation (UV) is established as a human carcinogen (1,2) although there is some scientific uncertainty about the exact relationship between sun exposure and skin cancer (3,4). The worldwide incidence of cutaneous (skin) melanoma is rising (2,(5)(6)(7), with approximately 100,000 new cases of skin cancer diagnosed yearly in the United Kingdom (UK), including around 7,000 new cases of malignant melanoma (8). The association between melanoma development and frequency of sunburn and sun exposure has been established (1,2,7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 The worldwide and UK incidence of cutaneous (skin) melanoma is rising. 2,5,6,7 In the UK, approximately 100,000 new cases of skin cancer are diagnosed yearly, which includes 7000 new cases of malignant melanoma. 8 The Health Protection Agency has named malignant melanoma as one of the four non-infectious diseases that will impact on future National Health Service (NHS) resources and create a largely preventable burden of disease.…”
Section: Introductionmentioning
confidence: 99%
“…The association between melanoma development and frequency of sunburn and sun exposure has been established, albeit without conclusive scientific evidence to fully interpret the causal relationship. 1,2,7 Lifestyle changes, such as increased overseas travel and greater outdoor leisure activities, have led to an increase in human exposure to sunlight. The depletion of the ozone layer coupled with the aesthetics associated with tanned skin, and use of artificial sources of tanning, means that UVR exposure is a serious worldwide public health issue for countries with large Caucasian populations.…”
Section: Introductionmentioning
confidence: 99%